Design and Implementation of IoT-Based Smart Aquarium using ESP32 for Water Quality Monitoring and Automatic Feeding - Yan Sofyan; Kuncoro Banu (Journal TIFDA (Technology Information and Data Analytic), 2026)
Advances in Internet of Things (IoT) technology have enabled the development of smart monitoring and automation systems across various application domains, including aquarium management. Conventional aquarium monitoring often relies on manual observation, which can be time-consuming and less effective for continuous environmental monitoring. This study aims to design, implement, and evaluate an IoT-based Smart Aquarium system utilizing the ESP32 microcontroller as the central controller. The proposed system integrates multiple environmental sensors, including temperature, pH, turbidity, and water level sensors, to acquire real-time aquarium data. Sensor measurements are processed by the ESP32 and transmitted to a cloud-based database, enabling real-time access through a mobile application. The developed platform also incorporates an automatic feeding mechanism using a servo motor, a monitoring camera for visual observation, and a solar panel subsystem as a supplementary energy source. Experimental results demonstrate that all sensor modules successfully acquired and transmitted environmental data to the monitoring platform. The mobile application was able to display real-time sensor readings and monitoring information through a centralized dashboard. Furthermore, the automatic feeding subsystem operated according to predefined schedules, while the camera monitoring and solar power subsystems functioned as intended. The results indicate that the proposed Smart Aquarium platform successfully integrates sensing, communication, monitoring, and automation technologies within a unified IoT ecosystem. The developed system provides an effective solution for real-time monitoring and remote aquarium management through the integration of embedded systems, cloud services, and mobile computing technologies.